Alexithymia is associated with aggressive tendencies following traumatic brain injury. (2nd January 2019) - Williams, Claire; Wood, Rodger Llewellyn; Howe, Holly
ABSTRACT: Objective : Aggressive behavior is a frequent legacy of traumatic brain injury (TBI). This study explores the question of how alexithymia, which is associated with deficits in social cognition and empathy, may predispose individuals to aggressive tendencies after head trauma. Method : A total of 47 individuals referred for routine neuropsychological assessment and advice on the management of long-term neuropsychological sequelae after TBI and 72 demographically matched controls completed the 20-Item Toronto Alexithymia Scale (TAS-20) and Buss Perry Aggression Questionnaire (BPAQ; self and proxy). Results : The incidence of alexithymia and aggressive tendencies was significantly higher in the group with TBI. After controlling for covariates, alexithymia explained an additional 29% of variance in BPAQ total scores in the group with TBI and 11.1% in the control group. Of the three TAS-20 sub-scales, ' difficulty describing feelings' emerged as a consistent unique predictor of aggression scores. Conclusions : Higher levels of alexithymia are associated with greater aggressive tendencies post-TBI. The findings offer important theoretical and empirical insights into the prediction of aggression after TBI.